2019
DOI: 10.3892/ol.2019.10299
|View full text |Cite
|
Sign up to set email alerts
|

Combination of quercetin and Adriamycin effectively suppresses the growth of refractory acute leukemia

Abstract: The present study aimed to investigate the effect of combined treatment with quercetin and Adriamycin (doxorubicin) on the development of refractory acute leukemia. Primary leukemic cells were isolated from patients with refractory drug-resistant acute leukemia. The Cell Counting Kit-8 assay was used to detect the proliferation of cells treated with a range of doses of Adriamycin, quercetin and a combination of the two drugs. Non-irradiated mice were used to establish a T cell acute lymphoblastic leukemia (T-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this regard, the coadministration of doxorubicin and quercetin significantly increased superoxide dismutase (SOD) activity and decreased malondialdehyde (MDA) content in the heart of mice. Therefore, combining quercetin and doxorubicin may enhance the effect of doxorubicin in treating leukemia [ 87 ]. Consequently, quercetin combined with cytosine arabinoside has been shown to improve leukemia treatment by inhibiting the formation of human leukemic cell colonies [ 88 ].…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…In this regard, the coadministration of doxorubicin and quercetin significantly increased superoxide dismutase (SOD) activity and decreased malondialdehyde (MDA) content in the heart of mice. Therefore, combining quercetin and doxorubicin may enhance the effect of doxorubicin in treating leukemia [ 87 ]. Consequently, quercetin combined with cytosine arabinoside has been shown to improve leukemia treatment by inhibiting the formation of human leukemic cell colonies [ 88 ].…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…In this regard, the co-administration of doxorubicin and Quercetin significantly increased Superoxide Dismutase (SOD) activity and decreased Malondialdehyde (MDA) content in the heart of mice. Therefore, combining Quercetin and doxorubicin may enhance the effect of doxorubicin in treating leukemia [87]. Consequently, Quercetin combined with cytosine arabinoside has been shown to improve leukemia treatment by inhibiting the formation of human leukemic cell colonies [88].…”
Section: Synergistic Effect Against Leukemiamentioning
confidence: 99%
“…Modern pharmacological studies have shown that quercetin can inhibit platelet aggregation, significantly inhibit platelet aggregation induced by thrombin and platelet activating factor, significantly inhibit the effect of cancer promoters, inhibit the growth of malignant cells in vitro, resist tumors, inhibit the expression of inflammatory mediators, and mediate cell signal transduction; Quercetin can inhibit the malignant proliferation of leukocytes, restore the hemogram to a relatively normal level, and has a significant inhibitory effect on ALL. [11,12] A number of studies have found that dihydroisoflavone E of Ophiopogon japonicus shows a variety of pharmacological activities, such as cardiovascular protection, anti-inflammatory, anti-cancer, antioxidant, immunomodulation, etc. [13] ; Homoplanin can play an anti-tumor role by inhibiting tumor cell proliferation, inducing tumor cell apoptosis, invasion and metastasis, tumor angiogenesis and other mechanisms, has multiple targets and a wide anti-tumor spectrum, plays a role in a variety of tumors, has weak toxicity to normal cells.…”
Section: Study On the Mechanism Of Msmy In The Treatment Of Allmentioning
confidence: 99%